Rancang Bangun Alat Pengupas Kulit Lidah Buaya - Prawatya, Yopa Eka; Fitrianti, Wanti; Sujana, Ivan (ELKHA : Jurnal Teknik Elektro, 2014)
Abstractâ€“ This article present the science and technology for society about applying of technology of aloe processing become the product owning economic value with the application of supporter equipments in order to optimalize productivity of aloe industry. Home industry of processing aloe in this time still conduct the production by using simple equipments which is disagree with method enase ( efficient, balmy, peaceful, effective and healthy). As application from three services of college at devotion aspect to society, through this science and technology program for society we design and build the aloe peeler to quicken the process of peel of husk of aloe and mince of aloe tea in order to product diversification and concern to the zero waste production so that give the amenity to middle and small industry in activity produce. Â  Keywords- Aloe, Ergonomic, Design and Build